Uji Efektifitas Ekstrak Daun Sirih (Piper Betle L.),Kirinyuh (Chromoloena Odorata) dan Tembelekan (Lantana Camara L.) Terhadap Populasi Nematoda Puru Akar (Meloidogyne Spp.) dan Pertumbuhan Tanaman Cabai (Capsicum Annuum L) - DWIPAYANA, MAGNA; WIJAYA, I NYOMAN; SRITAMIN, MADE (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.6, No.1, Januari 2017, 2017)
The Effectiveness Test of Extracts Of Betel Leaf (Piper Betle L.), Kirinyuh (Chromoloena Odorata) and Tembelekan (Lantana Camara L.) Against The Population of Root Knot Nematodes (Meloidogyne Spp.) and Plant Growth of Chili (Capsicum Annuum L.) Meloidogyne spp. was one of the parasitic nematode pests on crops of chili. Meloidogyne spp. was widespread in tropical regions and subtropik area.. Attacks of Meloidogyne spp. at the root can lower the production of the crops by 15 – 60 percent, even can reach 70 percent when the disease attacks vulnerable plants (Prihanto,1989). This research was carried out in a way controlling root knot nematodes on chili uses extract of 3 species of plants in a variety of concentrations with the aim to obtain a concentration from the plants that are very effective at suppressing the development of root knot nematodes and can suppress the population in the soil and as well to surpress the attacks on plant roots.The types of plants that will be used in this research is kirinyuh (Chromolaena odorata), tembelekan (Lantana camara) and betel leaf (Piper betle) in different concentrations to know their ability to suppress populations of root knot nematodes of chili. The leaves of the plant contains useful materials to suppress plant pests including root knot nematodes. From the three of leaf extract that have been used, the betel leaf extract effectively suppress the populations of nematodes on crops of chili for being able to put pressure against the population of the nematode in the soil or plant roots of chili. At the concentrations of 50 cc/polybag betel extracts are able to suppress the nematode population to 93% and on the concentration of 200cc/ polybag betel extracts was able to suppress populations of nematodes were 96.4%.
Keywords: Piper betle L., Lantana camara Linn., Chromoloena odorata Linn., Capsicum annuum L., Meloidoyne spp.